Effect of adherence to treatment guidelines on overall survival in elderly non-small-cell lung cancer patients - Lindqvist Jonatan; Jekunen Antti; Sihvo Eero; Johansson Mikael; Andersén Heidi (ELSEVIER IRELAND LTD, 2022)
Objectives
Mean age at diagnosis of lung cancer is increasing with increasing age in Western populations. The present study was designed to evaluate the effect of adherence to first-line treatment guidelines on overall survival (OS) in elderly patients with non-small-cell lung cancer (NSCLC) and reasons for non-adherence to treatment guidelines.
Materials and methods
All patients aged ≥ 65 years diagnosed with NSCLC in Ostrobothnia, Finland, during the years 2016 to 2020 were identified from hospital registries. Adherence of first-line treatment to contemporary treatment guidelines was analysed based on diagnosis, tumour stage and performance status (PS), as was the effect of adherence on OS.
Results
A review of hospital registries identified 238 NSCLC patients aged ≥ 65 years. Guideline adherence by stage decreased significantly with age, with 66.4% of patients aged 65 to 74 years, but only 33.3% of those aged > 80 years treated according to guidelines (p < 0.001). Other factors associated with non-adherence to guidelines included poor PS, frailty, and limited lung function. Of the patients with PS 0–2, 26.9% were under-treated according to guidelines. Reasons for under-treatment included comorbidities, decreased lung function, physician decision to reduce treatment intensity or recommend best supportive care, patient choice and PS decline before treatment initiation. Guideline adherence increased overall OS of elderly NSCLC patients in all stages. Elderly PS 2 patients appear to benefit from guideline adherence and active treatment. In contrast, active treatment did not benefit patients with PS 3–4.
Conclusions
Guideline adherence was associated with increased OS in elderly NSCLC patients. Almost 10% of elderly and otherwise fit NSCLC patients were not treated according to guidelines and could have benefitted from more intensive treatment.